2022
DOI: 10.1177/21925682211039835
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Socio-Economic Impact of Degenerative Cervical Myelopathy Is Fundamental to Improving Outcomes [AO Spine RECODE-DCM Research Priority Number 8]

Abstract: Study Design: Literature Review (Narrative). Objective: To contextualize AO Spine RECODE-DCM research priority number 5: What is the socio-economic impact of DCM? (The financial impact of living with DCM to the individual, their supporters, and society as a whole). Methods: In this review, we introduce the methodology of health-economic investigation, including potential techniques and approaches. We summarize the current health-economic evidence within DCM, so far focused on surgical treatment. We also cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…This aims to assess the financial impact of living with DCM on the individual, their caregivers and society as a whole. Davies et al 14 estimated the cost of DCM on society in the United Kingdom. They reported that the annual cost of admission and treatment alone amounted to £38,900,000 whereas the annual cost to society was estimated to be as high as £681,600,000.…”
Section: Discussionmentioning
confidence: 99%
“…This aims to assess the financial impact of living with DCM on the individual, their caregivers and society as a whole. Davies et al 14 estimated the cost of DCM on society in the United Kingdom. They reported that the annual cost of admission and treatment alone amounted to £38,900,000 whereas the annual cost to society was estimated to be as high as £681,600,000.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, disability and socioeconomic cost remain high 10a in DCM, while research investment and activity relatively low. 11a New and practice relevant insights have emerged from a multicentre collaboration.…”
Section: Commentsmentioning
confidence: 99%
“…These symptoms commonly include gait dysfunction, imbalance and falls, loss of strength and manual dexterity, and pain. Despite current best practice,6 a minority of patients will make a full recovery and DCM is often associated with lifelong disability, impaired quality of life and significant costs to both the individual and to society 7 8…”
Section: Introductionmentioning
confidence: 99%
“…So far, AO Spine RECODE-DCM has established the top research priorities and agreed on a single definition and index term 4 8 21–32. It has also agreed on ‘what’ should be measured in DCM research: that is, a minimum data set, which is comprised core data elements (CDE) and a core outcome set (COS).…”
Section: Introductionmentioning
confidence: 99%